Co-metabolic degradation of chlorobenzene by the fluorobenzene degrading wild strain Labrys portucalensis - Moreira, Irina S. (2013)
Due to the widespread use of chlorobenzene (CB), environmental contamination with this compound is a major concern. A previously isolated bacterium named Labrys portucalensis (strain F11), that is able to use fluorobenzene (FB) as sole carbon and energy source, was tested for its capability to degrade CB. Strain F11 was able to partially degrade CB only when F11 cells were previously grown in FB. Biodegradation of 0.5 mM of CB was achieved at a rate of 7.95 0.39 mmol l 1 day 1 with concomitant stoichiometric release of 50% of the chloride, while degradation of 1 mM of this compound resulted in 85% degradation at a rate of 16.9 0.81 mmol l 1 day 1 and with a 15% chloride release on the basis of the amount of compound biodegraded. Total CB biodegradation and dechlorination was only achieved when FB was also supplied to F11 cultures, suggesting cometabolic transformation. Total degradation of 0.5 mM of CB and 0.5 mM of FB occurred simultaneously at degradation rates of 105 6.07 mmol l 1 day 1 and 126 16.2 mmol l 1 day 1 respectively, with stoichiometric halogen release. Growth yield was lower when both substrates were present, suggesting synergistic inhibition. To our knowledge, this is the first time that co-metabolic biodegradation of CB in the presence of the fluorinated analogue is reported.